IMPLEMENTING JIGSAW II STRATEGY TO IMPROVE THE READING COMPREHENSION - Refai Refai (Premise: Journal of English Education and Applied Linguistics, 2012)
The objective of the study was to know whether the Jigsaw II can improve the 11th Graders’ reading comprehension. The findings revealed that Jigsaw II improved the students’ reading comprehension. At first, the teacher activates the prior knowledge of the students, then, explains the procedure of the strategy, then, the students discuss in jigsaw groups and in expert ones. In addition, the students do reading comprehension quizzes, the teacher determines the students’ scores.